Single-Phase and Binary Phase Nanogranular Ferrites for Magnetic Hyperthermia Application - Casagrande-Denardin, J (Blackwell Publishing Inc., 2020)
The study demonstrates the performance of heating efficiency in single-phase and binary phase spinel ferrite nanosystems. Ferrimagnetic cobalt ferrite (CoFe2O4) (CFO) and superparamagnetic copper ferrite/copper oxide (CuFe2O4/CuO) (CuF) nanosystems of different particle sizes were synthesized through a microwave-assisted coprecipitation method. The heating behavior was observed in range of both field amplitudes (8-24 kA/m at 516 kHz) and frequencies (325-973 kHz at 12 kA/m). The heating efficiency was analyzed and compared by means of particle size, magnetization, effective anisotropy constant, and Néel relaxation mechanism. Indeed, the heating rate was maximized in larger ferrite particles with low effective anisotropy constant. Moreover, though the magnetization and effective anisotropy constant of single-phase CoFe2O4 nanoparticles were higher, the binary phase CuFe2O4/CuO nanosystems of similar crystallite size (28 nm) exhibited superior heating efficiency (4.21°C/s). For a field amplitude and frequency of 24 kA/m and 516 kHz, the heating rate of CuF and CFO ferrites with different crystallite sizes decreased in the order of 4.21 > 2.14 > 0.58 > 0.52°C/s for 29 nm > 25 nm > 12 nm > 15 nm, respectively. The results emphasize that binary phase ferrite nanoparticles are better thermoseeds than the single-phase ferrites for the magnetic hyperthermia application. © 2020 The American Ceramic Society